Fabricated of Doping and Co-doing Cadmium Sulfide (CdS) Thin Films via Spray Pyrolysis for High-Efficiency Photovoltaic Window Layers (2015–2025) :A Comprehensive Review Artical (مجلة الفاروق للعلوم, 2026)
This review provides a comprehensive quantitative and systematic analysis of the development of spray-deposited, doped, and co-doped cadmium sulfide thin films used as optical windows in solar cells during the period from 2015 to 2025. Based on 25 peer-reviewed studies, this work classifies a wide range of dopers into: Group III elements (aluminum, gallium, indium), Group I acceptors (sodium, silver, copper), transition metals (barium, nickel, cobalt, manganese, zinc), rare earth elements (europium, praseodymium, dysprosium), and synergistic co-doping systems (aluminum-sodium, gallium-potassium, magnesium-cobalt, tin-zinc, aluminum-lanthanum). Analysis of variation reveals that the resulting stable hexagonal phase (wurtzite) is present in 72.0% of published studies. Quantitative scanning spectroscopy identifies an optimal doping window at μ=3.00 atomic. With an ±0.81% (σ=±0.81% atomic), this achieves a blueshift in the optical band gap (according to Burstein-Moss) averaging 2.45 eV (σ=±0.02 eV) and a transparency of 70–85%. Exceeding this value leads to the deposition of amorphous secondary phases at the grain boundaries, generating lattice stress and a 56.0% reduction in grain size (
Keywords: Cadmium Sulfide – Doping - Co-doping - Spray Pyrolysis -Thin Films – Photovoltaics - Window Layer